2016
DOI: 10.1371/journal.pone.0156600
|View full text |Cite
|
Sign up to set email alerts
|

Subspecific Differentiation Events of Montane Stag Beetles (Coleoptera, Lucanidae) Endemic to Formosa Island

Abstract: Taxonomic debates have been carrying on for decades over Formosan stag beetles, which consist of a high proportion of endemic species and subspecies featuring morphological variations associated with local adaptation. With the influence of periodical Pleistocene glaciations and the presence of several mountain ranges, the genetic differentiation and taxonomic recognition, within this medium-size island, of two endemic subspecies for each of four montane stag beetles, i.e. Lucanus ogakii, L. kanoi, Prismognathu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“… Hosoya and Araya (2005) reconstructed the first molecular phylogeny of stag beetles (based on the molecular markers cox1 and rrnL ) although using a small data set of only Japanese species. There has been particular attention to species delimitation and conservation of lucanids from Japan and Taiwan Island, partly because these beetles are popular as pets in these places ( Huang and Lin 2010 , Kubota et al 2011 , Lin et al 2011 , Tsai et al 2014 , Tsai and Yeh 2016 ). Kim and Farrell (2015) performed the first comprehensive phylogenetic study, and revealed a Gondwanan origin of Darwin’s stag beetle.…”
mentioning
confidence: 99%
“… Hosoya and Araya (2005) reconstructed the first molecular phylogeny of stag beetles (based on the molecular markers cox1 and rrnL ) although using a small data set of only Japanese species. There has been particular attention to species delimitation and conservation of lucanids from Japan and Taiwan Island, partly because these beetles are popular as pets in these places ( Huang and Lin 2010 , Kubota et al 2011 , Lin et al 2011 , Tsai et al 2014 , Tsai and Yeh 2016 ). Kim and Farrell (2015) performed the first comprehensive phylogenetic study, and revealed a Gondwanan origin of Darwin’s stag beetle.…”
mentioning
confidence: 99%
“…Phylogenetic trees inferred from molecular combined data show that both forms in sauteri and pseudocylindriformis groups are monophyletic reciprocally with high support values (Figs 2, 5). The weak phylogenetic resolution inferred from the 28S rDNA fragments of Pintung form and C. pseudocylindriformis might be due to the conserved property of 28S rDNA applying to resolve the relationship of closely related species (Guerra et al 2016; Tsai and Yeh 2016). Phylogenetic inferences, molecular dating, and the deep barcoding gap indicate that the different forms are genetically distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could be simply the result of sequence manipulation mistakes such as those we discovered. Nevertheless, K15 has already reached “highly cited” status in ISI (accessed 2 March 2017), and five of those citing articles (Aardema and Andolfatto, ; Padula et al., ; Rönkä et al., ; Tsai and Yeh, ; Wallbank et al., ) espouse their paper as a source of evidence for phylogenetic discordance, introgression and/or hybrid speciation.…”
Section: Discussionmentioning
confidence: 99%